Family experiences and viewpoints of palliative and supportive care for children with cancer: Can we do better? - du Plessis, Johannes (Department of Public Health and Family Medicine, 2017)
Background: The palliative and supportive care needs of children with cancer and their families are unique and require special attention. Children and their families in Africa facing lifethreatening/ life-limiting diseases have unique needs and have the right to achieve effective and evidence-based care. Development of appropriate services sensitive to the needs of families and based on observed evidence has become more and more recognized. As an introduction to develop and improve supportive and palliative care services for children with cancer, families were questioned regarding their experiences and suggestions for improvements. Methods: Sixteen family members of children with cancer and treated at Universitas Academic Hospital, Bloemfontein, South Africa, were questioned regarding their children's standard oncology and supportive/palliative care. Their responses were studied and repeating themes were identified. Results: A number of areas of need were identified: erratic psychosocial support, minimal financial support, poor parental access to basic needs and food provision, preventable errors in procedures and lack of sibling support. Staff were also not always sufficiently equipped to attend to palliative care patients. Conclusions: Supportive and palliative care for children with cancer needs to be improved. Family members are a valuable resource and the interviews identified a number of themes, valuable to consider in the expansion of a supportive/palliative care service. The intension of the study was to create the awareness that by making small and affordable changes, the quality of care that children and families receive can be improved.